The Financial Position Of Youth Employee: Pinning-Up Of Financial Capability And Income - Ni Nyoman Sawitri; Agus Zainal Arifin (Jurnal Akuntansi, 2021)
The aim of the study on the financial behavior of youth employees is to review the impact of financial capability, income on financial behavior in evaluating the financial position. The main target of this study is mediating the evaluation of financial behavior in the effort of increasing the financial position of youth employees. A research method conducts with a survey of 100 youth employees in Indonesia, particularly in Central Jakarta, that has more youth employees. Data from youth employees obtain through questionnaires and data is processed by SmartPLS; remember that analysis technique is using the path analysis model. Research results found that financial capability and income have a truly significant impact on financial behavior; likewise, it is directly to financial position. However, it known that financial behavior cannot directly influence to financial position. Research novelty explains that financial behavior cannot be mediation between financial capability and income to financial position. This finding is useful for youth employees in understanding the financial position and for the government in comprehending the financial behavior of youth employees. So, it expects to be able to give the policy of financial management for youth employees.